KEUNGGULAN KOMPETITIF DAN KOMPARATIF USAHATANI MANGGIS DI KABUPATEN TANGGAMUS - Andala, Angga; Abidin, Zainal; Situmorang, Suriaty (Lampung University, 2014)
This study aims to analyze the competitive and comparative advantages of mangosteen farm in Tanggamus Regency. The respondents were 45 farmers. Sample based on the age of the plant, from a number of farmers who have the same age plants and selecting a simple random sampling. The data was analyzed by PAM (Policy Analysis Matrix) analysis model. Assumption for the economic age of the mangosteen plant was 20 years. The results showed that the private revenue was Rp164,288,020 and social revenue was Rp397,293,431. Private profit was Rp35,207,465 and social profit was Rp266,725,184. Based on the analysis of competitiveness, it showed thatÂ Â mangosteen farm in Tanggamus Regency had comparative and competitive advantages, in which PCR values ââ0.764 and DRCR 0.300. Mangosteen farm in Tanggamus was sensitive to a decrease in output production by 20%, and a decrease in output prices by 30%. Keywords: competitiveness, mangosteen, PAM, sensitivity